2022
DOI: 10.3390/ani12030325
|View full text |Cite
|
Sign up to set email alerts
|

RNA-Seq Analysis of the Key Long Noncoding RNAs and mRNAs Related to the Regulation of Acute Heat Stress in Rainbow Trout

Abstract: As the global climate warms, more creatures are threatened by high temperatures, especially cold-water fish such as rainbow trout. Evidence has demonstrated that long noncoding RNAs (lncRNAs) play a pivotal role in regulating heat stress in animals, but we have little understanding of this regulatory mechanism. The present study aimed to identify potential key lncRNAs involved in regulating acute heat stress in rainbow trout. lncRNA and mRNA expression profiles of rainbow trout head kidney were analyzed via hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…In our study, Atlantic salmon, European seabass, Gilthead seabream and Grouper were mostly oceanic species, but their reactive mode barely might explain the decrease in muscle lipid content at higher temperatures. 363 Also, many other researches have focused on the mechanism of Rainbow trout temperature stress, 364,365 and it has been proven that the degree Celsius of water is the primary determinant of its short-term survival. 366 Our research further confirmed that when fed with plant oils instead of fish oil, the mode of lipid accumulation of Rainbow trout largely depends on water temperature.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, Atlantic salmon, European seabass, Gilthead seabream and Grouper were mostly oceanic species, but their reactive mode barely might explain the decrease in muscle lipid content at higher temperatures. 363 Also, many other researches have focused on the mechanism of Rainbow trout temperature stress, 364,365 and it has been proven that the degree Celsius of water is the primary determinant of its short-term survival. 366 Our research further confirmed that when fed with plant oils instead of fish oil, the mode of lipid accumulation of Rainbow trout largely depends on water temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Also in this sense, the idea was launched that long noncoding RNAs (lncRNAs) can be used in the selection of genetic variants of heat-resistant trout, given their essential role in the regulation of heat stress by association with genes involved in immune regulation, apoptosis and signaling pathways of metabolic activity [9].…”
Section: Introductionmentioning
confidence: 99%